Epigenetic memory and parliamentary privilege combine to evoke discussions on inheritance. - Fisher, A; Brockdorff, N (2012)
Understanding the basis of epigenetic memory is a fast-moving challenge in modern biology. At a recent Company of Biologists Workshop held at Steyning's historic Wiston House, thirty researchers led by John Gurdon interrogated three central questions: how are cell type-specific programs generated, what mechanisms duplicate this programmatic information as cells divide, and how does epigenetics contribute to trans-generational inheritance? We report some of the emerging themes arising from this debate.